Revivalism and Reconstructionism in Islamic Reform: Intellectual Trends in Modernist Maghribi Thought - Tais, M. Amine (The journal of religion & society, 2019)
Modernist Islamic thought has grown in a variety of ways for the last two centuries. This paper argues that two distinct directions can be detected in the works of contemporary Muslim thinkers in the Maghrib, namely revivalism and reconstructionism. These two intellectual trends were already present as tendencies in tension within the contributions of early modernist reformers. Since the second half of the twentieth century, they have evolved into two distinct perspectives that have formulated two different projects of reforming Islam. The writings of influential feminist Muslim thinkers Fatima Mernissi and Asma Lamrabet provide us with instructive examples of reconstructionism and revivalism respectively.